Does Buyer Power Contribute to Environmental Sustainability Performance in Supply Chains? - Appiah, Listowel Owusu; Abul- Majeed, Salifu (International Journal of Sustainable Development & World Policy, 2021)
Sustainability issues have gained the widespread attention of researchers and policymakers across the globe. Resultantly, studies on sustainability in supply chains and its associated relational and structural mechanisms are rife. This study has examined how the amount of power wielded by a buying organization affects its ability to lead the sustainability charge, to improve the environmental compliance among firms within the supply chain. The study adopted a quantitative approach for data analysis and reporting. A survey of 116 construction and Manufacturing and construction firms in Ghana. Data was collected using a structured questionnaire and analyzed using ordinary least squares (OLS) regression procedure using the PROCESS macro in SPSS. The findings of this study reveal a significant positive relationship between buyer power, collaboration with suppliers, and environmental sustainability performance. This study has implications for large corporations that are the target of stakeholder pressures, and small firms that need to corporate with their supply chain partners on the sustainability front.